Avaliação de pastos com capim elefante sob os sistemas de produção orgânico e convencional - Bratz, Vinicius Felipe (2016)
The objective of this research was to evaluate the forage production, stocking rate and nutritive value of elephant grass in organic and conventional systems. In the organic system, were combined species with complementary growth periods; the elephant grass was planted in rows 3 m apart from each other; between rows of elephant grass, the annual ryegrass was seeding in the cool season and the development of spontaneous growing species in the warm season. In the conventional production two pastures were studied, one with the same strategy of organic production but with mineral fertilization, and the other elephant grass was cultivated alone. It was applied 120 kg of N ha-1 with mineral and organic fertilizer (manure of cattle and pig slurry) in the conventional and organic systems, respectively. Lactating Holstein cows were used in the evaluation. The experimental design was completely randomized with three treatments (grazing systems), three replicates (paddocks) with repeated measures (grazing cycles). The pre and post forage mass parameters, botanical and structural composition, forage production and stocking rate were evaluated. Forage samples were collected by the hand-plucking method to determine the organic matter, mineral matter, crude protein, neutral detergent fiber, in situ organic matter digestibility. During the experimental period (370 days), nine grazing cycles were performed in organic and conventional systems (elephant grass in association of other plants) and eight grazing cycles in the conventional system (elephant grass alone). Forage production, stocking rate and crude protein of elephant grass were 31.9; 32.6; 24.2 t of dry matter ha-1; 3.4; 2.1; 4.6 animal units ha-1 and 16.6; 14.9; 13.6 %, respectively for the grazing systems. Considering the herbage yield, better performance were foud on mixture pastures. Higher values of crude protein were observed in the organic system.